Reproductive effects of cadmium on sperm function and early embryonic development in vitro - Zhao, Li-lin (PLoS One, 2017)
Cadmium is a major environmental toxicant that is released into the atmosphere, water and soil in the form of cadmium oxide, cadmium chloride, or cadmium sulfide via industrial activities, such as the manufacturing of batteries and pigments, metal smelting and refining and municipal waste incineration. In the present study, we investigated the effects of cadmium exposure on sperm quality parameters, fertilization capacity and early embryonic development. Our study showed that in vitro incubation of human or mouse sperms with cadmium for a long time (up to 24 hours) could significantly decreased sperm motility in a concentration- and time-dependent manner. Exposure to cadmium in the environment for a short term (30 min) did not affect sperm motility but significantly reduced in vitro fertilization rate. We also evaluated the effects of cadmium at concentrations of 0.625 μg/ml, and 1.25 μg/ml on early embryonic development in vitro and observed that the blastocyst formation rate dramatically decreased with increasing cadmium concentration. This finding emphasizes the hazardous effects of cadmium on sperm quality as well as on natural embryo development and raises greater concerns regarding cadmium pollution.